An investigation of microperimetry in macular function monitoring of retinal vascular diseases, their treatment and visual rehabilitation - Morales-Arroyo, Marco U. (2021)
Age-related macular degeneration (AMD) and diabetic eye disease are two of the main causes for blindness and severe visual loss in developed countries. Late AMD may be in the exudative, or neovascular form, whilst the main cause of visual loss in diabetic eyes is caused by an increase in microvascular endothelial permeability which leads to macular oedema. Treatment outcomes have improved considerably with the introduction of intravitreal therapies that inhibit vascular endothelial growth factor (VEGF). However, the advanced form of macular diseases can result in a progressive and irreversible loss of the central retina, affecting central vision including the capacity to fixate. In contemporary clinical practice, assessment of retinal pathologies typically includes visual acuity, fundal examination, and optical coherence tomography (OCT), which has been established as the gold standard for the management of retinal pathologies. However, since it is a diagnostic technique based exclusively on the structural image, it does not offer the possibility of evaluating functional data regarding visual function. Microperimetry (MP) technology assess functional characteristics of the retina, however, is not commonly used in retinal clinical practices. This research poses two questions related to the use of MP: the optimisation and standardisation in the clinical practice. It aims to understand and clarify the benefits of retinal functional analysis performed with the latest generation of MP instruments.